SISTEMATIC LITERATURE REVIEW TENTANG DILEMATIKA DAN PROBLEMATIKA WANITA KARIR: APAKAH MENDAHULUKAN KARIR ATAU RUMAH TANGGA TERLEBIH DAHULU? [SYSTEMATIC LITERATURE REVIEW ON CAREER WOMEN'S DILEMATICS AND PROBLEMS: DOES CAREER OR HOUSEHOLD FIRST?] - Salma Husniyati (Journal of Contemporary Islamic Counselling, 2021)
Career women are women who enter the professional world with the support of expertise both in terms of education and skills for career development purposes. Career women who are married have their own challenges in carrying out their duties and responsibilities. Not only prioritizing work tasks, married career women must also prioritize household duties and responsibilities. multitasking and time management are put to the test and see how much they can do. Duties and responsibilities in both roles can be completed properly if there is support from the parties involved, especially the support from the husband. In this paper, a systematic review of previous articles related to the theme is carried out. The results obtained based on the review are that the absence of multitasking skills, good time management, and support from the parties involved can hinder the performance of a career woman's dual role.